Science and nordic skiing (Meyer & Meyer Sport (UK) Ltd., 2007)
Between June 18-20 2006, the Vuokatti Sports Institute in Finland - arguably the world's finest ski training facility - played host to the International Congress on Science and Nordic Skiing."Science and Nordic Skiing" brings together the very latest in cutting edge research and developments into Nordic Skiing - ski jumping and cross-country skiing to biomechanics and the effects of cold weather on exercise - presented by some of the world's foremost experts in the field."Science and Nordic Skiing" is destined to become an invaluable and practical reference for sports scientists, coaches, skiers and anyone involved in this exciting area of winter sports.It presents the very latest research and development in the world of science and Nordic skiing.